Corporate entrepreneurship and ICT: trends and future research agenda - Funko, Ivana Sučić (2022)
Despite the breadth in the scope of scholarly literature concerning both Corporate Entrepreneurship (CE) and Information and Communication Technologies (ICT) respectively, intersectional research of these two domains is scarce. This paper explores whether and to what extent ICT and digital transformation (DT) are recognized within the CE research domain. Based on the analysis of articles indexed in the Web of Science Core Collection database - considered one of the most influential sources, with various records offering citation for numerous different academic areas - this study reveals six predominant research trends: Entrepreneurial Orientation, Digital transformation (DT), Innovation, Performance, Entrepreneurship, and Technological Change.